2022
DOI: 10.3389/fpubh.2022.944085
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction in Socio-Demographic, Academic, and Psychological Profile of College Students During the COVID-19 Pandemic in the Czech Republic and Slovakia

Abstract: Internet addiction is a serious problem among young adults that requires increased attention, especially at a time of distance learning during the coronavirus disease 2019 (COVID-19) pandemic. The aim of the study was to assess the relationships between internet addiction and selected socio-demographic, study-related, and psychological characteristics of college students. Internet addiction was measured using the Internet Addiction Test both overall and in its individual subscales (Salience, Excessive Use, Neg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 92 publications
2
21
1
Order By: Relevance
“…Epidemiological studies before the pandemic outbreak reported lower prevalence rates of IA among university students (approximately 11%) [ 104 , 105 ]. Our findings are in line with the studies conducted during COVID-19 that have reported prevalence rates of IA between 21% and 27% among young adult students [ 106 , 107 ]. This increase in the rates of IA prevalence during the COVID-19 pandemic could be due to the parallel increase in internet usage [ 6 , 20 ], as our study has also evidenced.…”
Section: Discussionsupporting
confidence: 93%
“…Epidemiological studies before the pandemic outbreak reported lower prevalence rates of IA among university students (approximately 11%) [ 104 , 105 ]. Our findings are in line with the studies conducted during COVID-19 that have reported prevalence rates of IA between 21% and 27% among young adult students [ 106 , 107 ]. This increase in the rates of IA prevalence during the COVID-19 pandemic could be due to the parallel increase in internet usage [ 6 , 20 ], as our study has also evidenced.…”
Section: Discussionsupporting
confidence: 93%
“…Although researchers have examined IA in university students, there are few studies to understand IA in college students under the pandemic, who are "forced" to have online learning and communication. Existing research reported a high prevalence of IA in university students under the COVID-19 pandemic: Jahan et al (2021) reported that around 71% of Bangladeshi university students showed symptoms of IA; Olawade et al (2020) found that 55% of university students in Nigeria could be classified as having IA; Gavurova et al (2022) reported that rough one-third of students in Czech Republic and Slovakia could be classified as having excessive symptoms of IA. Some related studies have been conducted in mainland China: Jiang et al (2020) and Xia et al (2021) reported prevalence rates of IA to be 32.4% and 30.6%; Cai et al (2021) found that 23.3% of the students could be regarded as having IA; Lin (2020) argued that school closure, social distancing restrictions, and related consequences had led students to heavily rely on the internet for meeting their psychosocial needs, hence increasing their risk of developing IA.…”
Section: Internet Addiction In University Students Under Covid-19mentioning
confidence: 99%
“…There are studies showing that failure to meet the daily needs and confrontation with challenges and difficulties would lead to psychological morbidity , which might predispose young people to be addicted to the internet. There are also studies showing that negative emotions are precursors of IA (Fernández-Villa et al, 2015;Gavurova et al, 2022).…”
Section: Internet Addiction In University Students Under Covid-19mentioning
confidence: 99%
“…On the other hand, the prevalence of PUF was 37.1% in the present study, which is similar to previous Bangladeshi studies by Sayeed 33 . Outside of Bangladesh, a multi-country study reported that the prevalence rates of PUI were 14% in South Korea, 19% in China, 35% in Hong Kong, 37.5% in Malaysia, 48% in Japan, 51% in the Philippines, 43.4% in Egypt, 30.8% in Czech, and 33.1% Slovak [42][43][44] . Prevalence rates for Facebook addiction has been identified as 47% in Malaysia 45 , 5.1% in Turkey 46 , and 26% in India 47 .…”
Section: Discussionmentioning
confidence: 99%